2007
DOI: 10.1007/s11064-007-9374-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nitric Oxide in Spatial Memory Deficits in Status Epilepticus Rats

Abstract: Status epilepticus (SE) is associated with a significant risk of cognitive impairment, and the increase of nitric oxide (NO) releasing has been reported during SE. We investigated the effects of neuronal nitric oxide synthase (nNOS) inhibitor, 7-nitroindazole (7-NI) and inducible nitric oxide synthase (iNOS) inhibitor, aminoguanidine (AG), on spatial performance of rats in the Morris water maze. Treatment with 7-NI, but not with AG, improved the performance of rats after SE not only in acquisition of the task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 55 publications
(58 reference statements)
2
8
0
3
Order By: Relevance
“…2). These data indicate that prolonged seizures early in life can cause long-standing cognitive impairments in object recognition memory, which corroborates with another work that observed that SE can induce memory impairments in animals subjected to the Morris water maze and inhibitory avoidance tasks (de Oliveira et al, 2008;Kubová et al, 2004;Liu et al, 2007). SE induces massive neurodegeneration in several brain regions, including the hippocampus and perirhinal cortex (Wang et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…2). These data indicate that prolonged seizures early in life can cause long-standing cognitive impairments in object recognition memory, which corroborates with another work that observed that SE can induce memory impairments in animals subjected to the Morris water maze and inhibitory avoidance tasks (de Oliveira et al, 2008;Kubová et al, 2004;Liu et al, 2007). SE induces massive neurodegeneration in several brain regions, including the hippocampus and perirhinal cortex (Wang et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…These discrepancies might be due to a high dose which was used for a long period in our previous study. Additionally, in another study AG did not affect learning and memory in spatial task in rats with status epilepticus [59]. In contrast, treatment with AG also ameliorated hypoxia-induced retrograde memory impairment in Balb/ c mice [60].…”
Section: Discussionmentioning
confidence: 89%
“…The study of Cankurtaran et al 19 indicated that independent correlates are female sex, advanced age, depression, and intake of vitamin supplements for AD; and depression and LDL-C for VaD. Some authors indicate that there is a relationship between cognitive status and NO levels, 26 whereas others have not found any. In the nervous system, NO seems to have both neurotoxic and neuroprotective effects, and it may have a role in the pathogenesis of stroke and other neurodegenerative disease, including AD associated with the activation of glial cells and the production of proinflammatory cytokines where the brain microvessels produce high level of NO.…”
Section: Discussionmentioning
confidence: 99%